Construct a 3D microsphere of HMX/B/Al/PTFE to obtain the high energy and combustion reactivity - Jian Wang; Jie Chen; Yaofeng Mao; Yongjun Deng; Wei Cao; Fude Nie; Jun Wang (Defence Technology, 2024)
Metal (aluminum and boron) based energetic materials have been wildly applied in various fields including aerospace, explosives and micro-devices due to their high energy density. Unfortunately, the low combustion efficiency and reactivity of metal fuels, especially boron (B), severely limit their practical applications. Herein, multi-component 3D microspheres of HMX/B/Al/PTFE (HBA) have been designed and successfully prepared by emulsion and solvent evaporation method to achieve superior energy and combustion reactivity. The reactivity and energy output of HBA are systematically measured by ignition-burning test, constant-volume explosion vessel system and bomb calorimetry. Due to the increased interfacial contact and reaction area, HBA shows higher flame propagation rate, faster pressurization rate and larger combustion heat of 29.95 cm/s, 1077 kPa/s, and 6164.43 J/g, which is 1.5 times, 3.5 times, and 1.03 times of the physical mixed counterpart (HBA-P). Meanwhile, HBA also shows enhanced energy output and reactivity than 3D microspheres of HMX/B/PTFE (HB) resulting from the high reactivity of Al. The reaction mechanism of 3D microspheres is comprehensively investigated through combustion emission spectral and thermal analysis (TG-DSC-MS). The superior reactivity and energy of HBA originate from the surface etching of fluorine to the inert shell (Al2O3 and B2O3) and the initiation effect of Al to B. This work offers a promising approach to design and prepare high-performance energetic materials for the practical applications.